Fish Assemblages in a Small Mangrove System on Príncipe Island, Gulf of Guinea - Cravo, Mariana; Almeida, Armando J.; Lima, Hamilton; Azevedo e Silva, João; Bandeira, Salomão; Machava-António, Vilma; Paula, José (Frontiers in Marine Science, 2021)
Mangroves are highly productive ecosystems with complex adaptations to the transition between freshwater and sea. Mangroves function as nursery habitats for many organisms, providing protection and food sources for early developmental stages of crustaceans and fish, helping to maintain adjacent marine stocks. Mangroves in São Tomé and Príncipe remain poorly studied. This study addresses the importance of a small mangrove stand to ichthyofauna. The main goal of the study was to describe the fish assemblages of the Praia Salgada mangrove stand on Príncipe Island, and assess if variations in the season, tide, and mangrove zone affected fish distribution. Fish assemblages were sampled with mosquito nets during the rainy and dry seasons, and neap and spring tides, while environmental parameters such as water depth, temperature, pH, and salinity measurements were taken. The characteristics of the water column were affected by a sandbank that developed between sampling seasons, impacting on the dynamics of the water and biological exchanges between the mangrove stand and the adjacent marine environment. The study identified 14 fish species occurring in the Praia Salgada mangrove stand from a total of 772 specimens caught. Five species were recorded for the first time as occurring in the country’s mangrove areas, namely Caranx latus, Ethmalosa fimbriata, Mugil curema, Gobioides cf. africanus, and Citharus cf. linguatula. Most of the reported species are of commercial interest, and were predominantly juveniles, suggesting that the mangrove ecosystem provides a nursery function for several species. Some species revealed preferences for either the upper or lower part of the mangrove forest. The size of fish sampled tended to be bigger during the dry season, especially for the Mugilidae, Aplocheilichthys spilauchen and Gobiidae groups. E. fimbriata and Eucinostomus melanopterus displayed similar sizes between seasons. The average quantity of fish caught per day in the rainy season was three times higher than in the dry season. The fish species distribution in the mangrove stand varied significantly according to the season and mangrove zone. The overall results suggest that the Praia Salgada mangrove stand provides a nursery function for several of the studied fish species.